MANHAJ AL-MUFASSIR AL-INDŪNĪSI AL-JĀWI FĪ AL-ISTIFĀDA MIN ASBĀB NUZŪL AL-QUR’ĀN ‘INDA TAFSĪRIHI LI AL-QUR’ĀN AL-KARĪM DIRĀSATAN TAḤLĪLIYYATAN - El-sharif, Abdul-Rahim (JOURNAL OF INDONESIAN ISLAM, 2025)
This study aims to conduct an analytical examination of the approach taken by the Indonesian commentator Muhammad ibn Umar al-Nawawi al-Jawi al-Bantani, known as Nawawi al-Jawi, in addressing asbāb al-nuzūl (the reasons for the revelation) of verses of the Holy Quran, through his interpretation of these verses in his book entitled ‘Maraḥ Labid’. The researcher employed a descriptive methodology to define asbāb al-nuzūl and clarify their conditions, and an inductive methodology to trace the examples of narrations mentioned by Nawawi al-Jawi in his commentary to illustrate these asbāb al-nuzūl. The researcher then employed an analytical approach to understand the strategy and methodology of the commentator Nawawi al-Jawi in presenting asbāb al-nuzūl. The research demonstrated that Sheikh Nawawi al-Jawi was meticulous in using asbāb al-nuzūl as an assistance to understanding the texts of the Holy Quran, and that he adhered to the principles of this discipline, deviating from them only in very rare instances.